Wittgenstein naturalizing language : from sublimation of logic in the tractatus to Its contextualization in the investigations - Salar, Ümit Ömür. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Wittgenstein develops his new philosophy in contrast to the Tractatus. With his guidance, we do this about ‘logic’ here: logic (i.e. essence) of language, and science of logic, i.e. philosophy (Chapter 1). We see the essence of Wittgenstein’s new view is contextualization: language does not possess any ‘formal unity’ but is a ‘family’ of phenomena (Chapter 2). The presumption that logic only deals with thought is dropped; activity is now part of logic. Similarly, philosophy moves from ‘logical analysis’ to examination of particular instances: “everything descriptive of a language-game is part of logic.” (On Certainty, §56; Chapter 3). Since philosophy itself employs language, it must itself belong to a context. This is achieved through philosophical problems (Chapter 4). We demonstrate Wittgenstein’s refutation of the Tractarian conception, and his solution of the Problem of Logic in Chapter 5: existence of concepts and language depends on, among other things, complete agreement in judgements (paradigmatic instances). In Chapter 6, we formulate the Methodological Impasse which the Tractatus fails to overcome: since we examine the nature of language by using language, what we say applies to itself, creating inconsistency. Wittgenstein now thinks any employment of language must do something if it is to have sense. His philosophizing has the function of solving philosophical problems. We too need such a function for this thesis to make sense: hence our application to the ‘Resolute Reading’ (Chapter 7). We prove its falsity, call for complete agreement in this judgment, and put an end to that reading.
Keywords: Wittgenstein, Ludwig, 1889-1951. Tractatus logico-philosophicus.; Logic, Symbolic and mathematical.; Language and languages -- Philosophy.